Pengaplikasian Metode Elemen Hingga Pada Kapal Landing Craft Tank Teluk Katurei Akibat Perubahan Fungsi Tangki - AGUS PRIHANTO, BAMBANG (Techno Bahari, 2022)
Landing Craft Tank (LCT) ships are vessels used to transport large vehicles such as heavy cargo, bulldozers, excavators, dumb trucks, loaders, and other heavy equipment indispensable for construction and mining work. For shipping locations that are transported using a Landing Craft - Tank (LCT) ship, it is a mining location or project location that is on an island or beach and river route which is indeed difficult to reach by ordinary transport vessels. The Landing Craft - Tank (LCT) ship has a broad and flat deck so it can carry heavy equipment and construction materials. The LCT Sarana III ship has a main size of Length Over All = 47.00 m, Breadth Deck = 9.50 m, Draft Design = 2.00 m, Dept = 3.20 m. As a result of this load it will result in load distribution on the LCT ship. With changes in the ship's framing system, there will be a change in voltage characteristics. In each framing system, the maximum stress analysis is carried out with the help of a numerical finite element method (FEM) program. The analysis used is the analysis of static loads originating from the vehicle, the load for each loading condition and the hydrostatic load. The analysis aims to determine the stress characteristics and the greatest stress value of ship construction and to determine the location of the critical point on the ship, based on three variations of loading conditions, namely calm water, sagging and hogging. The results of the analysis and calculations carried out on the LCT model one in calm water conditions of 68 N / mm2, sagging conditions of 76.8 N / mm2, and hogging conditions of 74.1 N / mm2. For model two in calm water conditions of 68 N / mm2, sagging conditions of 74.8 N / mm2, and hogging conditions of 72.6 N / mm2. From the results of the stress values, it can be concluded that all stress values that occur on the ship are still meet the safety factor, both according to the material criteria and BKI standards.